Imaginários, saberes e fazeres no ensino superior: processos formativos do formador de professores - Debus, Ionice da Silva (2017)
This thesis is part of the Training, Knowledge and Professional Development Teacher Line of the Post-Graduate Program in Education of the Federal University of Santa Maria, RS. This research started from the research problem about the specific knowledge and practices of the teacher training required for the teacher who graduated from the bachelor 's degrees who also worked in the baccalaureate courses. To do this, we seek to investigate and understand the imaginary about the specific knowledge and practices of the teacher training necessary for the teacher who graduated from the baccalaureate courses, to understand the imaginary significations of the teacher teacher about the formation of the future teacher; investigate and reflect on the imagery of the professors of the last degrees created at the Federal University of Santa Maria in relation to being a teacher. To do so, composing a qualitative research were heard six professors (two of each course), of the last degree courses created at the Federal University of Santa Maria, namely, Dance Degree, Social Sciences Degree and Theater Licenciatura. Thus, through the biographical method, from the oral narratives of the formative processes of these teachers and the analysis of the official documents that govern the courses were constructed the data. With the analysis we could understand that, from the imaginary and the sensitive-creative knowledge, the teacher who graduates from the degrees can ally to the various curricular components, the issues related to the human, the development of empathy skills, the exercise of looking and place of the other, for a collaborative work, interconnecting the most diverse knowledge that already make up the being a teacher. key words: Teacher training. University teaching. Professional teacher development. Social imaginary. Bachelor's degrees.